Reclamation of Herb Residues Using Probiotics and Their Therapeutic Effect on Diarrhea - Meng, Fanjing; Chen, Tingtao; Ma, Dongwen; Wang, Xin; Zhao, Xiaoxiao; Tian, Puyuan; Wang, Huan; Hai, Zhiwen; Shen, Liang; Tang, Xianyao; Wang, Xiaolei; Xin, Hongbo (Mediators of Inflammation, 2017)
Residues from herbal medicine processing in pharmaceutical plants create a large amount of waste (herb residues), which consists mainly of environmental pollution and medicinal waste. In order to resolve this problem, probiotics of Bacillus (B.) subtilis, Aspergillus (A.) oryzae, and Lactobacillus (L.) plantarum M3 are selected to reuse herb residue of Jianweixiaoshi tablets (JT), and an antibiotic-associated diarrhea (AAD) mouse model was established to evaluate the therapeutic effects of the herb residue fermentation supernatant. Our results indicated that the fermentation supernatant had scavenged 77.8% of 2,2-diphenyl-1-picrylhydrazyl (DPPH), 78% of O2•−, 36.7% of •OH, 39% of Fe2+ chelation, and 716 mg/L reducing power. The inhibition zones for Salmonella (S.) typhimurium, S. enteritidis, Shigella (Sh.) flexneri, Escherichia (E.) coli, Listeria (L.) monocytogenes, Sh. dysenteriae 301, and Staphylococcus (S.) aureus were 17, 14, 19, 18, 20, 19, and 20 mm, respectively. The in vivo results indicated that the fermentation supernatant resulted in a high diarrhea inhibition rate (56%, p<0.05), greatly enhanced the disruption of bacterial diversity caused by antibiotics, and restored the dominant position of L. johnsonii in the treatment and recovery stages. Therefore, the combination of the herb residue and probiotics suggests a potential to explore conversion of these materials for the possible development of therapies for AAD.